Propuesta de un modelo de gestión de incentivos estratégicos para mejorar el desempeño laboral en los trabajadores del Ministerio Público del Distrito judicial de Loreto 2023 - Zumaeta Gonzales, Oscar Alexis (2024)
Job performance is a sign of quality in any organization, which is why the objective of this study is to propose a management model of strategic incentives to improve job performance in workers of the Public Ministry of the Judicial District of Loreto. The sample population of this study was made up of 50 workers. We use the survey and the questionnaire to obtain the required information. The findings showed that 38% of employees have good job performance in the productivity dimension. Therefore, it seems likely that the incentive proposal is having a positive impact on the workforce, generating greater productivity. Likewise, 44% of employees exhibit good performance in the personal characteristics dimension. And finally, 34% of people in the expertise dimension have good job prospects.